2023
DOI: 10.3389/fcvm.2023.1190051
|View full text |Cite
|
Sign up to set email alerts
|

Associations of adenovirus-reactive immunoglobulins with atrial fibrillation and body mass index

Abstract: Adenovirus (AdV) has been suggested to be involved in pathogenesis of atrial fibrillation (AF). We aimed to evaluate an association between AdV-specific immunoglobulins G in the serum (AdV-IgG) and AF. The present case-control study comprised two cohorts, including cohort 1 of patients with AF and cohort 2 of asymptomatic subjects. Initially, two groups, MA and MB, were selected from the cohorts 1 and 2, respectively, for serum proteome profiling using an antibody microarray to identify possible relevant prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…A total of 192 patients completed the one-year follow-up period. Clinical and demographic characteristics of the total cohort have been described previously [ 15 ] and are shown in Table 1 . A history of AF was 4.0 ± 2.7 years, and the mean age at the AF onset was 53.24 ± 10.55 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 192 patients completed the one-year follow-up period. Clinical and demographic characteristics of the total cohort have been described previously [ 15 ] and are shown in Table 1 . A history of AF was 4.0 ± 2.7 years, and the mean age at the AF onset was 53.24 ± 10.55 years.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study profiled the proteins in the serum samples using the antibody microarray technology to discriminate patients with AF from normal subjects [ 15 ] and patients with coronary stenosis from patients with intact coronary vessels, and differential proteins were subsequently verified using an in-house ELISA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on healthy subjects with COVID-19 infection in anamnesis is very scarce. We have previously demonstrated that adenovirus infection may be an etiological factor of atrial fibrillation [ 5 ]. Thus, a viral infection may have harmful effects on cardiac function due to the mechanisms related to transcriptional and posttranslational modifications that disrupt the gap junctions, influence immune response, or mediate the development of cardiomyopathy during an active infection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%